A Comparative Study of The Effect of Humor Strategies on Iranian EFL Learners’ Vocabulary Learning - Najafi, Maryam; Shahrokhi, Mohsen; Shojaee, Maryam; Atharizadeh, Mahmood (International Journal of Language Education, 2021)
This paper aimed at examining and comparing the effects of different humor-based strategies (joke, pun, and limerick) on vocabulary learning of EFL learners at intermediate and advanced levels. To this end, 120 EFL learners in a private institute were asked to serve as the participants of the study. They were then divided into two groups according to their proficiency levels (i.e. advanced and intermediate). Each group contained four subgroups: three experimental groups (joke, pun, and limerick groups) and one control group. Before the treatment, the participants took part a pretest, which aimed to ascertain the homogeneity of the participants. The treatment for the three experimental groups then commenced, and it was followed by a vocabulary posttest. The data were gathered and analyzed via one-way between-groups ANOVA. The results revealed that for the intermediate learners, joke was more effective (although not significantly) than pun, which was (not significantly) more effective than limerick. The difference between joke and limerick, however, was statistically significant. For the advanced learners, the joke group outperformed both pun and limerick groups significantly. However, the difference between pun and limerick groups did not reach statistical significance. There was thus not a considerable difference between intermediate and advanced learners in terms of how they were affected by the treatments.